Respuesta :

Answer: [tex]3x - 11[/tex]

Step-by-step explanation:

Given :

[tex]f(x) = 3x - 5[/tex]

[tex]g(x) = x - 2[/tex]

to find [tex]f(x)[/tex] o [tex]g(x)[/tex] , we will first substitute g(x) , that is

[tex]f(x-2)[/tex]

The next thing is to substitute [tex]x-2[/tex] in place of [tex]x[/tex] in the value of f(x) , that is

[tex]f(x)[/tex] o [tex]g(x)[/tex] = [tex]3(x-2) - 5[/tex]

[tex]f(x)[/tex] o [tex]g(x)[/tex] = [tex]3x - 6 - 5[/tex]

[tex]f(x)[/tex] o [tex]g(x)[/tex] = [tex]3x - 11[/tex]